The Content and Design of Chinese Media Groups' Corporate Websites: An Empirical Study - Luo, Xiaofan (2007)
Corporate websites enable companies to communicate with a broad range of publics and address their different interests on sites respectively. Although corporate websites have existed for decades, there is hardly any simple standard or rules related to the content and design features. This dissertation has developed a framework to examine the corporate website of Chinese media groups. There are few researches on Chinese media groups, since they have been viewed as the apparatus of the government, but recent decades the nature of business has been highlighted. The framework differentiates website content features from design features. The content component addressing the different information needs of various stakeholders includes four dimensions. The design component contains usability, interactivity, security and credibility dimensions. This framework has been applied to examine the differences between four categories of Chinese media groups' corporate websites and between the corporate website of Chinese media groups and that of Western transnational media companies. The results of this research indicate that the distinctions of corporate websites between different categories of Chinese media groups are meaningful in five dimensions of content and design features, and the differences of sites between Chinese media groups and Western transnational media companies are very significant in four dimensions of content and design features.